Comparative Superovulatory Response, Embryo Recovery, and Embryo Quality in Holstein-Friesian and Limousin Donor Cattle in Indonesia - Anggita Dian Pramudhita; Detry Al Bukhary; Putri Utami; Habib Asshidiq Syah; Anny Rosmayanti; Putri Indah Ningtias; Fahrudin Darlian; Trinil Susilawati; Aulia Puspita Anugra Yekti (ANIMAL PRODUCTION, 2026)
Embryo transfer (ET) is a reproductive biotechnology used to accelerate the dissemination of superior genetics. However, its success under Indonesian tropical conditions remains variable and may be influenced by physiological and adaptive differences between dairy and beef cattle used as embryo donors. This study compared in vivo embryo production between Holstein-Friesian (HF) and Limousin donor cattle. The study was designed as a comparative observational study using selected donor cattle, comprising 11 HF and 25 Limousin cows maintained under standardized ET management. The observed parameters included superovulatory response, represented by the number of corpora lutea (CL), total ova/embryos collected, fertile embryos, transferable embryos, embryo quality, response rate, and recovery rate. Data were analyzed using descriptive statistics, and breed differences were analyzed using Welch’s independent t-test when variance heterogeneity was detected, and Cohen’s d was used to estimate effect size. Limousin cows showed higher CL counts than HF cows (12.72 ± 6.98 vs. 6.55 ± 2.88; P < 0.001), produced more total ova/embryos (11.44 ± 6.45 vs. 6.00 ± 3.00; P < 0.001), fertile embryos (9.16 ± 5.17 vs. 3.45 ± 2.81; P < 0.001), and transferable embryos (5.76 ± 4.29 vs. 1.91 ± 2.07; P < 0.001). Response rate between HF and Limousin cows was 94.12% vs. 92.86%, as was the recovery rate (89.92% vs. 90.12%). Overall, these findings indicate that under the conditions of this study, Limousin cattle exhibited higher superovulatory responses and embryo production than HF cattle, although breed-specific protocol optimization remains necessary.